2020
DOI: 10.1371/journal.pone.0232722
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors improving support for vaccinations among Polish primary care physicians

Abstract: In Poland, primary care physicians are the most used and most trusted source of information on immunisation. We aimed to explore factors influencing support for vaccinations among physicians employed in the childhood immunisation programme, in order to inform education of healthcare workers and programme organization. In June-July 2017, we carried out a national cross-sectional survey of physicians working in randomly selected primary healthcare practices, and interviewed them by telephone. We assessed support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 28 publications
4
25
0
2
Order By: Relevance
“…Indeed, when it has been measured with multivariate logistic regression analysis the relationship between the sources of information and the different outcomes of interest, it has been found that this source appears to have a significant influential impact on vaccination coverage since those who sought information from scientific journals were more prone to have positive attitude towards the effectiveness of vaccine in preventing HPV-related diseases in girls between 12–26 years compared to those who had not used such source. This result corroborated evidence that has already been proven in a lot of previous published investigations among different groups of the population that these sources are key in improving the level of knowledge, the attitudes, and the recommendation behaviors [ 10 , 23 , 24 , 25 ]. In addition, this is also important because increases in misinformation about vaccines may also limit or influence the acceptance, and with the pandemic emergency of COVID-19, there has been the shifting of healthcare resources with the accumulation of susceptible individuals and a higher likelihood of vaccine-preventable diseases outbreaks.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, when it has been measured with multivariate logistic regression analysis the relationship between the sources of information and the different outcomes of interest, it has been found that this source appears to have a significant influential impact on vaccination coverage since those who sought information from scientific journals were more prone to have positive attitude towards the effectiveness of vaccine in preventing HPV-related diseases in girls between 12–26 years compared to those who had not used such source. This result corroborated evidence that has already been proven in a lot of previous published investigations among different groups of the population that these sources are key in improving the level of knowledge, the attitudes, and the recommendation behaviors [ 10 , 23 , 24 , 25 ]. In addition, this is also important because increases in misinformation about vaccines may also limit or influence the acceptance, and with the pandemic emergency of COVID-19, there has been the shifting of healthcare resources with the accumulation of susceptible individuals and a higher likelihood of vaccine-preventable diseases outbreaks.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of Italian pediatricians scored low on vaccine knowledge [ 81 ], as did South African doctors [ 120 ]. Canadian HCPs showed knowledge gaps in pertussis and Tdap [ 38 ], Italian pediatricians and American PCPs in MenB disease and 4CMenB vaccine [ 93 , 104 , 108 ], and Israeli providers in childhood vaccines [ 107 ]. British GPs were less confident in their knowledge of pertussis than influenza vaccination; 59% desired further education [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…An Israeli study using multivariable analysis found knowledge to be associated with HCPs vaccinating their children according to the immunization program but not with their recommendation to others [ 113 ]. Self-perceived knowledge of Polish HCPs was positively associated with vaccination support, but this relationship no longer held when controlling for demographics and information source [ 108 ]. In another study, knowledge was only associated with recommendation in bivariate but not multivariate analysis, suggesting the influence of a third variable [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Według polskich danych z badania Narodowego Instytutu Zdrowia Publicznego -Państwowego Zakła du Higieny (NIZP-PZH) z 2017 r. (ankieta telefoniczna, 500 uczestników -lekarzy, którzy organizują i przeprowadzają powszechne szczepienia ochronne: 81% z nich to pediatrzy, 19% -lekarze medycyny rodzinnej) odsetek lekarzy regularnie szczepiących się przeciw grypie wynosił 62% [22].…”
Section: Poziom Zaszczepienia Przeciw Grypie Wśród Personelu Medycznegounclassified
“…Dane ogólnoeuropejskie UE/EOG wskazują maksymalnie 9,5% VCR (sezon 2012/13) [12], a w badaniu warszawskim (placówki szpitalne) podano, że zaszczepionych przeciw grypie jest 22,3% lekarzy oraz 10,6% pielęgniarek [41]. Dane ogólnopolskie NIZP-PZH z 2017 r. (lekarze placówek POZ) mówią o 62% zaszczepionych lekarzy [22]. Dużą zmienność potwierdzają dane zarówno z rejestrów europejskich (np.…”
Section: Interwencje Zwiększające Poziom Zaszczepienia Przeciw Grypie Wśród Personelu Medycznegounclassified